Sex in consumer culture : the erotic content of media and marketing - Reichert, Tom; Lambiase, Jacqueline (LEA's communication series., 2006)
Sex in Consumer Culture: The Erotic Content of Media and Marketing considers the use of sex to promote brands, magazines, video games, TV programming, music, and movies. Offering both quantitative and qualitative perspectives from leading scholars in a variety of disciplines, this volume addresses a range of integral issues such as media promotion, racial representations, appeals to gay and lesbian communities, content analyses, and case studies. Chapters represent diverse perspectives, addressing such questions as:*What happens when sexual content created for adults reaches chi.